Functional diagnosis of communication skills and needs of girls with ASD - Niemiec, Marta (Logopedia Silesiana, 2023)
This study is dedicated to recognising the issue of appropriate, accurate and reliable identification of communication needs and skills in the diagnostic process among girls/women with autism spectrum disorders. The present article describes changes in the approach to diagnosing people with ASD, the latest classifications and diagnostic criteria of the disorder in question. It characterises the deficits related to communicative competences in people with autism spectrum disorder and Asperger’s syndrome. Consideration is also given here to the specificity of the diagnostic assessment of girls/women with ASD and Asperger’s syndrome and the utility of using functional diagnosis and selected diagnostic tools to correctly identify the communication skills and needs of girls with autistic spectrum behaviours.